Conflict Resolution: a Challenge for Joint Forest Management in India - Rastogi, Alind (Indian Forester, 1999)
The present day ecological conflicts have their roots in economic compulsions, sociological stresses, technological intensification, changing consumption patterns, scarce land availability and contending resource users. Making trade-offs between competing goals is thus a necessary skill for the officials. Inventory of conflicts relate to resource use, structures, roles, interests, socio-Iegal and cultural attributes. However to decipher, understand and resolve the conflicts through effective communication, negotiation, mediation and conciliation poses a challenge before the natural resource manager. The paper stresses that the conflict resolution mechanisms are to be evolved, institutions developed and structures harmonised with the needs of Joint Forest Management (JFM) in India.